2021
DOI: 10.5539/jas.v13n11p54
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Farmer Capacity Building in Financial Resource Mobilization on Performance of Smallholder Irrigation Projects in Migori County, Kenya

Abstract: The study examined influence of farmer capacity building in financial resource mobilization on performance of smallholder irrigation projects in Migori County, Kenya. The study adopted pragmatism as its philosophy, and used cross sectional and correlation research design. The target population was 2,815, and comprised farmers from fifteen smallholder irrigation projects that receive water from River Kuja through Lower Kuja Project. The sample size was 341 farmers. The study used systematic random sampling to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The level of significance for the variable was 0.000<0.05, an indication that strategic innovation significantly determined competitiveness of third tier banks in Kenya. This compares with the assertions by Asawo et al (2021) that institutions where their leaders have the potential to be more innovative have a high likelihood of being competitive than where innovation is not upheld. Further, Likoko et al (2022) upheld that strategic innovation is an instrumental enabler of competitive firms by its ability to strengthen firm's uniqueness in the market and ability to meet customer needs.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The level of significance for the variable was 0.000<0.05, an indication that strategic innovation significantly determined competitiveness of third tier banks in Kenya. This compares with the assertions by Asawo et al (2021) that institutions where their leaders have the potential to be more innovative have a high likelihood of being competitive than where innovation is not upheld. Further, Likoko et al (2022) upheld that strategic innovation is an instrumental enabler of competitive firms by its ability to strengthen firm's uniqueness in the market and ability to meet customer needs.…”
Section: Resultsmentioning
confidence: 54%
“…A study by Asawo et al (2021) evaluated how funds contribute to performance among small enterprises in Kenya. The results showed that firm performance is highly dependent on organizational resources, and particularly finances.…”
Section: Empirical Reviewmentioning
confidence: 99%